The arbitral award and the powers of the arbitrator appointed by the court in accordance with the UAE arbitration law - Al-Ali, Zayed Saeed Salim Zayed (2023)
This study talked about the arbitral award and the powers of the arbitrator appointed by the court in accordance with the UAE Federal Arbitration Law No. (6) of 2018. This law regulates the procedures and methods to be followed in accordance with the UAE Arbitration Law and not violate public order. This study adopted a qualitative methodology through the descriptive، analytical and comparative method by extrapolating and analyzing the rules and texts of Federal Law No. (6) of 2018 on arbitration، compared to other legislation. This study aimed to clarify the nature of the arbitrator and arbitration، its legal status، and the similarities and differences between arbitration and the judiciary. This study showed that the UAE Arbitration Law sets legal rules and principles that obligate the parties to the arbitration and the arbitrators to settle the dispute within a certain period. Moreover، this study explained the rules related to the legal adaptation of the relationship that binds the litigants to the arbitrator، the arbitration center، and the nature of the arbitrator’s work. The study also dealt with the limits of the arbitrator، his powers and responsibility، the method of his selection by the court، and the arbitrator's authority to determine the applicable law. This study also differentiated between legal restrictions and the agreement in commercial arbitration. The results of this study showed that the Federal Arbitration Law No. 56 of 2018 regulated the internal arbitration rules، and the legislator did not stipulate these rules under independent procedural rules that clearly show how to organize the duties of the arbitrator and the scope of his responsibility to protect the rights of the contestants and strengthen the arbitration system. The study suggested that the UAE legislator organise the arbitration rules and establish comprehensive rules for all aspects of arbitrators and the arbitral system. In addition to reconsidering the establishment of provisions related to electronic arbitration in line with the development of the virtual world. Moreover، this study recommends setting up an arbitration system that is not limited to traders only، but rather opens the way to other categories of civil society.